Case report: Neuroendocrine carcinoma of the nasal cavity in a roe deer (Capreolus capreolus) - Vengušt, Gorazd; Vengušt, Diana Žele; Cantile, Carlo; Gombač, Mitja; Tekavec, Kristina; Švara, Tanja (Frontiers in Veterinary Science, 2025)
Neuroendocrine tumors of the nasal cavity are rare in both animals and humans. This report describes the macroscopic, histopathological and immunohistochemical characteristics of a neuroendocrine tumor in a three-year-old female roe deer (Capreolus capreolus) that was shot due to a facial deformity caused by an oval, firm, exophytic lesion effacing the left frontal and parietal regions. Longitudinal sectioning of the skull revealed a nasal cavity tumor that had invaded the cribriform plate, the rostral bones of the skull, the rostral aspect of the cranial cavity and the frontal sinuses and extended through the lacrimal, sphenoid and zygomatic bones into the subcutaneous tissue. Histopathologically, the tumor consisted of neoplastic cells forming sheets, nests, trabecular and cribriform structures separated by a delicate fibrovascular stroma. Mitoses were rare. Based on the histopathological and immunohistochemical findings, a neuroendocrine carcinoma was diagnosed. Based on thorough database searches, this is the first known case of a nasal neuroendocrine carcinoma in a roe deer.